2016
DOI: 10.1021/acs.jpcc.5b11706
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Sensing of Heat Transport at Solid–Liquid Interfaces

Abstract: We report experimental studies of interfacial heat transport for a system of Au nanodisks supported on fused silica substrates, coated by hydrophilic and hydrophobic self-assembled monolayers, and immersed in water−ethanol mixtures and solutions of a nonionic surfactant, hexyl-β-Dglucoside in water. The Au nanodisks are abruptly heated by a subpicosecond optical pulse; time-resolved changes in the temperature of the Au nanodisk and the liquid near the nanodisk/liquid interface are monitored by measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
(72 reference statements)
1
38
0
Order By: Relevance
“…This approach has for instance been used to measure the thermal conductances at the interface between metal nanoparticles and their environment, and to investigate the dependence of these conductances on composition of nanoparticles, environment and interfaces (e.g., nature and length of surfactant molecules). 7,[20][21][22][23] The relation between the measured time-resolved optical signals and the thermal kinetics in the nanoparticles and their local environment has also been recently modeled, 21,24,25 allowing more precise estimations of interface conductances in cases where environment heating significantly influences time-resolved signals. Additionally, some time-resolved experiments performed on arrays of metal nanowires patterned on crystalline substrates with high phonon mean free paths (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has for instance been used to measure the thermal conductances at the interface between metal nanoparticles and their environment, and to investigate the dependence of these conductances on composition of nanoparticles, environment and interfaces (e.g., nature and length of surfactant molecules). 7,[20][21][22][23] The relation between the measured time-resolved optical signals and the thermal kinetics in the nanoparticles and their local environment has also been recently modeled, 21,24,25 allowing more precise estimations of interface conductances in cases where environment heating significantly influences time-resolved signals. Additionally, some time-resolved experiments performed on arrays of metal nanowires patterned on crystalline substrates with high phonon mean free paths (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the effects of work of adhesion on interface thermal conductance. 34 Raman spectroscopy has proved to be a powerful tool for studying the thermal transport at micro/nanoscales. Several works were reported that shows the potential of this tool to investigate thermal conductivity and hot carrier diffusion coefficient of 2D materials, such as graphene 35,36 and transition metal dichalcogenides (TMD).…”
Section: Acoustic Mismatchmentioning
confidence: 99%
“…However, most of the techniques commonly used in nanofabrication involve a time‐consuming, expensive lithographic process and a high vacuum metal‐deposition process, which severely restricts the development of LSPR sensors in practical applications. Additionally, most recent studies have focused on the fabrication of metasurfaces on rigid substrates such as glass or fused silica . However, plastic substrates are becoming increasingly attractive, as such materials offer considerable merits over existing rigid substrates and are ideal for lightweight and disposable device applications.…”
Section: Introductionmentioning
confidence: 99%